THE EFFECT OF COMMUNICATION ON EMPLOYEE JOB MOTIVATION AND PERFORMANCE IN DELTA STATE BROADCAST ORGANIZATIONS - Ejiroghene AYEWUMI (Indonesian Journal Of Business And Economics, 2022)
The core of this study was to examine via inferential and descriptive statistics, the statistical correlation between organization communication on employee’s job motivation and job performance in the broadcast organizations in Delta State, Nigeria. This study was anchored on the unitary theory of industrial relations due to its relevance to the scope of this study. To achieve the general and specific objective of this study, the descriptive survey research design was adopted and primary data were obtained from questionnaire responses administered to one hundred and seventy-one staff of the seven broadcast organizations used for the study. Hypotheses were formulated and tested and findings emerged. This chapter therefore presents the summary of this study’s findings, conclusion, contribution to knowledge and recommendations.